Molecular characterization of African swine fever virus in apparently healthy domestic pigs in Uganda - Kalenzi Atuhaire, David; Ochwo, Sylvester; Afayoa, Mathias; Mwesigwa, Savannah; Mwiine, Frank Norbert; Okuni, Julius Boniface; Olaho-Mukani, William; Ojok, Lonzy (African Journal of Biotechnology, 2014)
African swine fever (ASF) is a highly lethal and economically significant disease of domestic pigs in Uganda where outbreaks regularly occur. There is neither a vaccine nor treatment available for ASF control. Twenty two African swine fever virus (ASFV) genotypes (I - XXII) have been identified based on partial sequencing of the C-terminus of the major capsid protein p72 encoded by the B646L gene. The majority of previously characterized Ugandan ASFV strains belong to genotype IX. The major aim of the current study was to determine the ASFV genotypes among asymptomatic slaughter pigs at Wambizi slaughterhouse and in some parts of the country where surveillance was done. Three discrete regions of the ASFV were analysed in the genomes of viruses detected in asymptomatic domestic pigs. The analysis was conducted by genotyping based on sequence data from three single copy ASFV genes. The E183L gene encoding the structural protein P54 and part of the gene encoding the p72 protein were used to delineate genotypes, before intra-genotypic resolution of viral relationships by analysis of tetramer amino acid repeats within the hypervariable central variable region (CVR) of the B602L gene. All the ASF viruses obtained from this study clustered with previous viruses in genotype IX based on analysis of the p72 and P54 genes. Analysis of the CVR gene grouped the viruses in three different subgroups; 13, 23 and 25. Only one genotype is circulating in Uganda among asymptomatic domestic pigs and it is the same virus causing outbreaks in the country and parts of neighbouring Kenya.
Keywords: African swine fever virus; Asymptomatic; Slaughterhouse; P54; CVR gene; Genotypes